2012
DOI: 10.2174/092986612802084546
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Nucleobindin-2 Inhibits 3T3-L1 Adipocyte Differentiation

Abstract: Nucleobindin-2 is a 420 amino acid EF-hand Ca2+ binding protein that can be further processed to generate an 82 amino terminal peptide termed Nesfatin-1. To examine the function of secreted Nucleobindin-2 in adipocyte differentiation, cultured 3T3-L1 cells were incubated with either 0 or 100 nM of GST, GST-Nucleobindin-2, prior to and during the initiation of adipocyte differentiation. Nucleobindin-2 treatment decreased neutral lipid accumulation (Oil-Red O staining) and expression of several marker genes for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…This finding extends the action of nesfatin-1 to brown adipocytes and provides further evidence supporting its critical role in the regulation of lipid homeostasis. Consistent with this observation, previous studies have demonstrated that nesfatin-1 inhibits lipid accumulation in 3T3-L1 cells16 and hepatocytes17, as well as reduces circulating fatty acid levels in diet-induced obese mice1718. NUCB2/nesfatin-1 is expressed abundantly in the X/A like cells of gastric mucosa and may be released into the circulation to exert actions in both central and peripheral tissues.…”
Section: Discussionsupporting
confidence: 73%
“…This finding extends the action of nesfatin-1 to brown adipocytes and provides further evidence supporting its critical role in the regulation of lipid homeostasis. Consistent with this observation, previous studies have demonstrated that nesfatin-1 inhibits lipid accumulation in 3T3-L1 cells16 and hepatocytes17, as well as reduces circulating fatty acid levels in diet-induced obese mice1718. NUCB2/nesfatin-1 is expressed abundantly in the X/A like cells of gastric mucosa and may be released into the circulation to exert actions in both central and peripheral tissues.…”
Section: Discussionsupporting
confidence: 73%
“…In addition to its originally identified function to inhibit dark cycle food intake, nesfatin-1 exhibits a broad array of actions, ranging from effects on glucose metabolism [11], inhibition of gastric acid secretion [15] and gastrointestinal motility [16], control of fluid and electrolyte homeostasis [17], inhibition of adipogenesis [18], counteracting NO-dependent vasodilation [19], to cardio-protection against ischemia/reperfusion injury [20]. Among these functions, the effects of nesfatin-1 on glucose homeostasis and its potential mechanisms remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…3A). Different from that found in gastric mucosa, the NUCB2 detection by western blot in adipose tissue presented one only band at 50 kDa as previously described in the bibliography for this tissue with the same antibody Ramanjaneya et al, 2010;Tagaya et al, 2012). Conversely to protein expression the NUCB2 mRNA expression peak was at 6 weeks of age (2 weeks old: 1.01 ± 0.06, 4 weeks old: 1.31 ± 0.17, 6 weeks old: 1.50 ± 0.14 and 8 weeks old: 0.98 ± 0.06 arbitrary units; **p < 0.01) (Fig.…”
Section: Age-associated Variations In Nucb2/nesfatin-1 Levelsmentioning
confidence: 49%